Effect of white guava (Psidium guajava L.) fruit juice on the quality of lead acetate induced rats (Rattus norvegicus) spermatozoa - Alifia, Annisa; Sri Mulyati; Wurlina Wurlina; Tatik Hernawati; Budi Utomo; Soeharsono Soeharsono; Sri Agus Sudjarwo; Muhammad Thohawi Elziyad Purnama (Universitas Airlangga, 2023)
This study aims to determine the effect of the administration of white guava (Psidium guajava L.) fruit juice on spermatozoa plasma membrane integrity (PMI), morphological abnormality, viability, and motility of lead acetate induced rats (Rattus norvegicus). Twenty-five male rats were divided into five groups: NC (negative control) group, rats were administered with distilled water twice daily at four-hour intervals; T0 (positive control) group, rats were administered daily with lead acetate 50 mg/kg bw and distilled water four hours later; T1, T2, and T3 groups, rats were administered daily with lead acetate 50 mg/kg bw and 0.5 mL of 25, 50, and 100% white guava fruit juice four hours later. The treatment of the rats was conducted for 14 days, and on day 15, all rats were sacrificed to assess the spermatozoa quality. Data was analyzed using ANOVA followed by Duncan's multiple range test at a confidence level of 95%. The results showed that exposure to lead acetate (T0) caused lower spermatozoa PMI, viability, and motility as well as higher spermatozoa morphological abnormalities (p <0.05) compared to those of the T0 group. Administration of white guava fruit juice starting at a dose of 25% (T1) resulted in higher spermatozoa motility, viability, and PMI as well as lower spermatozoa morphological abnormalities (p <0.05) compared to rats in the T0 group. It could be concluded that white guava fruit juice maintained the spermatozoa quality of lead acetate induced rats.